2011
DOI: 10.1074/jbc.m111.223438
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Soluble Receptor for Advanced Glycation End Products (sRAGE)

Abstract: Background: RAGE is a multiligand cell surface receptor involved in various human diseases. Results: The solution structure of human sRAGE was determined. sRAGE oligomerization is concentration-and calcium-dependent. Conclusion:The monomer displays a J-like shape; the dimer is elongated and forms through association of two N-terminal domains. Significance: This paves the way for the design of new therapeutic strategies for a large number of pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 31 publications
4
36
1
Order By: Relevance
“…Thus, RAGE is likely to integrate combinations of inflammatory stimuli, and drive appropriately adjusted immune responses. The activity of RAGE is also regulated by concentration and metal ion-dependent cis-or trans-homodimerization (Koch et al, 2010;Sárkány et al, 2011) and the soluble RAGE form has been shown to interfere with RAGE dimerization and signaling (Hofmann et al, 1999;Bierhaus et al, 2001). Thus, fine-tuning of RAGE activation is likely an important mechanism for timely detection of microbes and sterile tissue damage.…”
Section: Rage-deficient Mice Have Impaired Inflammatory Responses To mentioning
confidence: 99%
“…Thus, RAGE is likely to integrate combinations of inflammatory stimuli, and drive appropriately adjusted immune responses. The activity of RAGE is also regulated by concentration and metal ion-dependent cis-or trans-homodimerization (Koch et al, 2010;Sárkány et al, 2011) and the soluble RAGE form has been shown to interfere with RAGE dimerization and signaling (Hofmann et al, 1999;Bierhaus et al, 2001). Thus, fine-tuning of RAGE activation is likely an important mechanism for timely detection of microbes and sterile tissue damage.…”
Section: Rage-deficient Mice Have Impaired Inflammatory Responses To mentioning
confidence: 99%
“…Thus, RAGE, a pattern recognition receptor [3537], may recognize negative charge and/or hydrophobicity on its ligands. There are several positively charged patches on the V-domain of RAGE, including Arg-29, Lys-37, Lys-39, Lys-43, Lys-44, Arg-48, Lys-52, Arg-98, Arg-104, Lys-107, Lys-110, Arg-114 and Arg-116 [33,38,39], which may form two main regions [39] that interact with negatively charged regions of RAGE ligands (e.g., Aβ, S100 proteins, age-modified compounds and HMGB1) (Figure 2B). RAGE also has a number of hydrophobic pockets, which include residues Ile-26, Ala-28, Ile-30, Pro-33, Leu-34, Val-35, Leu-36, Trp-61, Val-63, leu-64, Trp-72, Val-75, Val-78, Leu-79, Pro-80, Phe-85, Leu-86, Pro-87, Ala-88, val-89, Ile 91 and Tyr-118 [33,39].…”
Section: Structure–function Relationship Of Ragementioning
confidence: 99%
“…In a mouse model of AD, PD-hAPP, sRAGE increased CBF and reduced neuroinflammation and brain Aβ levels by acting as a decoy receptor that sequesters the Aβ and preventing it from interacting with membrane bound RAGE [5]. However, RAGE is known to self-associate and forms oligomers via the C1 domain [2,38]. Ligand binding may stabilize the RAGE oligomers that lead to transmembrane cell signaling.…”
Section: Rage Isoformsmentioning
confidence: 99%
See 2 more Smart Citations